The complete mitochondrial genome of the invasive house crow Corvus splendens (Passeriformes: Corvidae). (3rd March 2016) - Krzeminska, Urszula; Wilson, Robyn; Rahman, Sadequr; Song, Beng Kah; Gan, Han Ming; Tan, Mun Hua; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the invasive house crow ( Corvus splendens ) was sequenced (GenBank accession number: KJ766304) using the MiSeq Personal Sequencer (Illumina, San Diego, CA). The mitochondrial genome is 16, 962 bp in length, comprising 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal subunit genes and a non-coding control region. The mitogenome structural organization is identical to that of the other Corvus species and related genera. The overall base composition of C. splendens is 30.65% for A, 29.71% for C, 14.84% for G and 24.80% for T, with an AT content of 55.45%. We propose to use full mitochondrial genome to address taxonomic issues and to study the population genetics of crows.